Body composition assessment among adults in Thika, Kiambu county, Kenya - N., Mututho L.; K., Kiboi W.; N., Waihenya R. (International Journal of Research in Medical Sciences, 2019)
Background: Research has shown that body composition is directly related to health. Altered body composition, can greatly increase the risks of conditions such as cardiovascular disease and diabetes. Bioelectrical Impedance Analysis fosters early detection of an improper balance in the body composition, which allows for earlier intervention and prevention. Methods: This was a cross sectional analysis of body composition for adults who volunteered to be screened during a Nutrition week in Kiambu County, Kenya. A total of 301 adults were included in the assessment. Body Mass Index (BMI) and Body composition (body fat %, bone mass, muscle mass, visceral fat and water %) were measured using bioelectrical impedance analysis. Results: The age of the participants ranged from 18-99 years (mean 42.19±16.57 years). Most of the participants were males (53.5%). More than half (53.2%) of the participants had a poor BMI, 37.2% had high total body fat percentage, 12.6% had excess levels of visceral fat and 26.6% had poor water hydration status. Age (OR=0.095; p value <0.001; CI 0.033-0272) and visceral fat (r=0.74; p value <0.001) were significantly associated with the BMI. Females had a significantly higher BMI (P <0.001). Visceral fat was also positively correlated with age: r=0.74; P value <0.001. Conclusions: Sex, age and BMI were important determinants of body composition. Increased physical activity, appropriate dietary practices are crucial in maintaining a healthy BMI and body composition. For timely intervention regular nutrition screening should be promoted among different populations.